What differentiates sexual from non-sexual homicides? A case–control study - de Oliveira, Gustavo Carvalho (International journal of comparative and applied criminal justice, 2025)
Research comparing sexual homicide (SH) and non-sexual homicide (NSH) has been rare outside North America and Europe and has contributed to addressing whether SH is primarily a sexual or homicide offence or a hybrid. This case–control study compared 142 SH and 142 NSH cases from Australia and New Zealand. Bivariate analyses indicated SH offenders more often had sexual problems, lacked intimacy, and appeared more prosocial, had less serious mental health problems, with lifestyles giving opportunities to access victims. Planning rather than reacting, sexual fantasies and arousal, time, and isolation to interact with victims privately, control of victims and crime scenes, lack of remorse, reliving the experience later, preventing detection, and more intrusive, intimate, and sadistic interactions characterised SH offences. Victims were more likely to be strangers, unrelated, single, and living alone. We developed multivariate models to predict SH, with the final model including: offender single, with a sexual disorder, but not a substance use disorder or major mental illness; offence long in duration, with expressive physical violence and unusual or ritualistic features, against a stranger, in an isolated location. These results are consistent with previous studies and indicate SH is different from NSH, supporting differential practice with SH. However, the findings could primarily reflect the over representation of sexual sadism in SH and the over representation of intimate partner victims in NSH. Future research needs to consider the heterogeneity of SH.